A RAPID IN VITRO METHOD FOR THE EVALUTION OF CANDIDATE REPELLENTS AGAINST LEPTOTROMBIDIUM CHIGGERS - Rodkvamtook, W.; Prasartvit, A.; Gaywee, J.; Jatisatienr, C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Scrub typhus is an acute febrile zoonotic disease resulting from infection with the Gram-negative intracellular bacteria Orientia (formerly Rickettsia) tsutsugamushi (Hyachi) (Seong et al. 2001). The disease is endemic in much of south and central Asia, with approximately one million cases each year and more than a billion people at risk worldwide (Rosenberg 1997). Scrub typhus is transmitted by several species of larval trombiculid mites which are commonly known as chiggers (Tanskul et al. 1998). Repellents provide an effective method of protecting individuals from arthropods (Gupta and Rutledge 1994). In this study 6 essential oils were tested to evaluate their repellent activity against the chigger, Leptotrombidium imphalum Vercammen-Grandjean and Langston. A rapid and economic in vitro procedure which requires only 5 min and a small number of chiggers was used to determine the median effective doses. The results showed that clove oil was significantly more effective than others with ED50 of 53.2 µg followed by vetiver oil (<4.0 mg), orange oil (6.31 mg), oil of Zingiber cassumunar Roxb. (6.40 mg) and turmeric oil (32.6 mg) whereas oil of Boesenbergia rotunda (Linn.) Mansf. expressed slight efficiency only.